ANALISIS KURIKULUM 2013 - Nurhasanah, Ana; Adya Pribadi, Reksa; Nur, M. Dapid (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2021)
Education is the foundation of a country's progress. In this case, education has a very important role to improve the quality of human resources to support and meet personal needs or even the needs of a country. Education will run well and structured if there is a directed education system. One of them in the education system is the curriculum as an implementer and reference in the movement of education. Indonesia itself currently uses the 2013 curriculum as its educational curriculum. The 2013 curriculum replaces the old curriculum, namely KTSP (Education Unit Level Curriculum) or the 2006 curriculum. It is necessary to analyze the 2013 curriculum in order to find out the advantages and disadvantages of the 2013 curriculum. Because the curriculum will continue to evolve with the times. This 2013 curriculum analysis uses a qualitative approach research method with interview and observation instruments to convey experiences. The results of this study are expected to be used as study material for students, schools, and academics.